Q: What is 7a 6 simplified?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3a + 4a +/- 6; take the 3a & 4a and combine them; 7a +/- 6 would be your answer as 6 cannot combine with 7a due to the variable. If 7a +/- 6 = 0, then subtract/add (respectively) the 6 depending on the operation. Therefore 7a + 6 = 0 turns to 7a = -6. Divide the 7 with the -6 to get the a alone; a = -6/7 or -0.8. Cannot be simplified.

7A + 3

(7a + 35)/-7 = 7(a + 5)/-7 = -(a + 5) = (-a - 5)

7a + 6 = -36 Subtract 6 from both sides: 7a = -42 Divide both sides by 7: a = -6 a = -6

a + 18 = 7a a-a +18 = 7a-a 18 = 6a 18/6 = 6a/6 3 = a 3=a

Related questions

It is: 3a+7a = 10a simplified

7(a-2b)-6(a-4b) 7a - 14b - 6a - 24b 7a - 6a - 14b - 24b a - 38b

It is: 2a+5a = 7a when simplified

7a

It is: 7a+1 when simplified

3a + 4a +/- 6; take the 3a & 4a and combine them; 7a +/- 6 would be your answer as 6 cannot combine with 7a due to the variable. If 7a +/- 6 = 0, then subtract/add (respectively) the 6 depending on the operation. Therefore 7a + 6 = 0 turns to 7a = -6. Divide the 7 with the -6 to get the a alone; a = -6/7 or -0.8. Cannot be simplified.

It is: -7a when simplified

It can be simplified to: -45a-15

7A + 3

(7a + 35)/-7 = 7(a + 5)/-7 = -(a + 5) = (-a - 5)

7a + 6 = -36 Subtract 6 from both sides: 7a = -42 Divide both sides by 7: a = -6 a = -6

The variable is a. You can solve for it, like this: 8a - 9 = 7a - 6 8a = 7a + 3 8a - 7a = 3 a = 3